Evaluation of Cases with Disability Rate Calculated Due to Medical Malpractice - Demir, Burhan; Soğukpınar, Veysel Osman; Terece, Cem; Sönmez, Mehmet Mesut (The Bulletin of Legal Medicine, 2025)
Objective: In this study, cases in which disability rates were calculated due to medical malpractice were evaluated. The decisions of the of the relevant specialized committee are discussed in the light of the literature in relation to many different parameters, and it is aimed to identify the problems that need to be considered and prevented in this regard.Methods: In this study, 233 cases whose disability rates were calculated by the Third Specialized Board of Forensic Medicine of the Forensic Medicine Institute  between 01/01/2015 and 31/12/2019 due to medical malpractice were retrospectively analyzed. Results: In this study, 47.2% of the patients were male and 52.8% were female. 61% of the cases were examined by the relevant specialty board. Medical malpractice lawsuits were most commonly filed after having treated in private hospitals. Disability was determined in 163 of the cases. Only specialist physicians are responsible for 77.3% of medical malpractice cases. Ophthalmology and Pediatrics were the specialties with the highest disability rates. In 23 of the 24 cases with a calculated disability rate of 100%, the specialist physician was responsible for medical malpractice, and the most common branch among these was Pediatrics.Conclusion: Disability rates after medical malpractice are higher in Pediatrics and Ophthalmology. Studies on disability due to medical malpractice should be conducted separately for each clinic. According to the results of the study, key issues to be considered by physicians should be identified to prevent patient disability due to medical malpractice.
Keywords: Forensic Medicine; Medical Malpractice; Disability